Analisis SWOT Dalam Pengembangan Produk Usaha Rumahan Donut’s Amira - Wanti, Eny Trisno; Yunita, Tyna (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This research aims to determine the SWOT (Strength, Weakness, Opportunity, Threat) analysis of the MSME (Micro, Small and Medium Enterprise) "Donut's Amira) business owned by Mrs. Nopy which is located in Gabus, North Tambun. The business "Donut's Amira" is one of the MSMEs which operates in the culinary sector, especially donuts. This research uses a qualitative approach using data collected through interviews. It is hoped that this research can fulfill the author's curiosity regarding the SWOT analysis of the "Donut's Amira" business. Through this program, it is hoped that it can open up job opportunities for the community.